2009
DOI: 10.1002/da.20417
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the mechanisms of hoarding from an experimental perspective

Abstract: Future research with this experimental task can separately investigate the role of acquisition, retention, impulsivity, and sensitivity to constraints in clinical hoarding to inform our understanding of this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 49 publications
2
29
0
Order By: Relevance
“…[45,62] Characteristics, such as perfectionism and uncertainty, are common to both compulsive hoarding and OCD. [25,39,45,46,50,64] Unlike OCD, however, compulsive hoarding patients display no exaggerated beliefs associated with the importance of or control over thoughts. [45,65] Overlapping with some symmetryrelated obsessions, touching or moving possessions without permission provokes great distress in hoarding patients and reflects an excessive desire to maintain control over possessions.…”
Section: Should Hoarding Continue To Be Mentioned As a Symptom Of Anomentioning
confidence: 99%
“…[45,62] Characteristics, such as perfectionism and uncertainty, are common to both compulsive hoarding and OCD. [25,39,45,46,50,64] Unlike OCD, however, compulsive hoarding patients display no exaggerated beliefs associated with the importance of or control over thoughts. [45,65] Overlapping with some symmetryrelated obsessions, touching or moving possessions without permission provokes great distress in hoarding patients and reflects an excessive desire to maintain control over possessions.…”
Section: Should Hoarding Continue To Be Mentioned As a Symptom Of Anomentioning
confidence: 99%
“…Most studies of the behavioral and cognitive aspects of HD have utilized neutral contexts that did not test decisions about discarding actual items, or modeled discarding using imaginary scenarios (Frost et al, 1998; Preston, Muroff, & Wengrovitz, 2009) without testing actual discarding behavior. Only Tolin and colleagues (Tolin et al, 2009; Tolin, Stevens, Villavicencio, et al, 2012) used an experimental discarding task involving personal possessions; they found that HD participants showed different patterns of neural activity while discarding compared to healthy controls.…”
Section: Hypothesismentioning
confidence: 99%
“…Future studies might investigate the temporal dynamics of decision making to examine changes in neural activity from earlier to later stages, using behavioral tasks that are well suited for that purpose. 67 …”
Section: Commentmentioning
confidence: 99%